2020
DOI: 10.1186/s12917-020-02365-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characteristics of multi-drug resistant Streptococcus porcinus from the vaginal secretions of sow with endometritis

Abstract: Background: Sow endometritis is a common disease in pig breeding farms after artificial insemination, which leads to gray-green vaginal secretions and decreased conception rates. It is important to perform an etiologic diagnosis for effective treatments and control of diseases. The aim of this study was to carry out a pathogenic detection in five specimens of vaginal secretions collected from sick pigs with endometritis, implement identification of the pathogens by phenotypic detection and 16 s rDNA sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
9
1
1
Order By: Relevance
“…Thus, hardly any investigations on S. porcinus have been published recently. In contrast to previous reports [ 26 ], we could not recover S. porcinus from the CNS, urogenital tract or joints.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, hardly any investigations on S. porcinus have been published recently. In contrast to previous reports [ 26 ], we could not recover S. porcinus from the CNS, urogenital tract or joints.…”
Section: Discussioncontrasting
confidence: 99%
“…It is also related to cases of endometritis in swine after artificial insemination in farms. Antibiotic resistance is prevalent in this species, with some strains resistant to erythromycin, streptomycin, tetracycline, aminoglycosides, quinolones, macrolides, and others [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It not only causes infertility in humans and animals but also leads to economic losses due to unfavorable effects on survival, productivity, and animal welfare (2,3). It is reported that in some large farms of China, 47.6% of sows were culled due to various abnormalities, of which 41.4% were culled due to endometritis, and even severe endometritis in sow can also cause sepsis and death (4,5). The causes of endometritis are very complex.…”
Section: Introductionmentioning
confidence: 99%